PENGARUH FINANCIAL LITERACY DAN LIFESTYLE TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA DI SIDOARJO DENGAN PERILAKU KONSUMTIF SEBAGAI VARIABEL MEDIASI - Virginia Eka Putri Kinanti; M. Mustaqim; Wahyu Eko Pujianto; Cynthia Eka Violita (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the impact of financial literacy and lifestyle on personal financial management of Sidoarjo students, considering consumption behavior as a mediating variable. To do this, quantitative methods were used, specifically targeting Sidoarjo university students. Data were collected using questionnaires, using purposive sampling techniques in non-probability sampling. Financial literacy, lifestyle, and consumptive behavior variables directly affect financial management. Financial literacy variables mediated by consumptive behavior also impact financial management. However, lifestyle variables mediated by consumptive behavior do not affect financial management. The mediating effect of financial literacy variables on financial management through consumption behavior is high. On the other hand, lifestyle variables have no impact on consumption behavior and the mediation effect is weak.